Marketing Strategy of Educational Services in Improving the Image of Institutions at Institut Agama Islam Al-Quran Al-Ittifaqiah Indralaya - Alfirdausi, Muhammad Ulul Albab; Waspodo, Waspodo (Yayasan Sembilan Pemuda Indonesia, 2024)
The purpose of this study is to identify and analyse the marketing strategies used by the Institut Agama Islam Al-Quran Al-Ittifaqiah Indralaya (IAIQI) to improve the image of their institutions. This study aims to address the following issues: (1) Analysis of the marketing strategy carried out by the IAIQI to enhance the image of the institution. The research method used is a qualitative approach. The data collection procedure involves the collection of information from Deputy Rector I and Deputy Rector III, as well as students and the public acting as informants. Data collection is done through observations, interviews, and documentation. The most effective promotional efforts undertaken by the IAIQI include advertising, word marketing, public relations, and collaboration. In order to enhance the reputation of educational at IAIQI, cooperation efforts are being made by these institutions in partnership with the government as well as with national and international public and private colleges, high schools, and teachers. Based on this research, SWOT analysis shows that the right strategy to use is the SO strategy, which is to take advantage of the power over the existing opportunities. It can be concluded that the marketing strategy of educational services in improving the image of institutions like IAIQI has been implemented by making planning through identification, segmentation, differentiation, and marketing mix elements quite well. However, it would be even better to document the promotion activities thoroughly for further improvement.